Unsettling: Transgression and Travel in the Literature of the Medieval North Atlantic - DeAngelo, Jeremy P (OpenCommons@UConn, 2014)
This project examines the significance of travel, both as practice and metaphor, in Anglo-Saxon literature, placed in the context of the neighboring traditions of the Irish and the Icelanders. It identifies in early Irish, Anglo-Saxon, and Norse literature a metaphor wherein one’s literal movement (“conduct”) in the story represents their behavior (“conduct”) in life. Using the poem The Whale as its test case, it describes the Christian concept of discretio spirituum (“the Discernment of Spirits”) as a tool for distinguishing good conduct from bad. With these terms established, the project examines actual travelers in Anglo-Saxon literature for lessons in conduct. Outlaws, which are well-represented in the literature, display more explicitly than most travelers the idea of “transgression,” which like conduct is taken both literally and metaphorically as the crossing of boundaries. Outlaws challenge sedentary society in numerous ways, both for good and ill, and the dissertation looks at outlaw traditions in Ireland, Iceland and England and at Beowulf, a hero with outlaw elements, and Guthlac, a saint who was once an outlaw, to see how transgression, when properly applied, was seen to benefit both religion and society. The last chapter examines the poem Andreas, a work which argues in favor of travel in its depiction of a reluctant missionary who becomes an adventurous traveler. The project culminates with a look ahead at post-Conquest England, where outlaw figures such as Hereward the Wake herald new standards of conduct and transgression in an altered North Atlantic society.